Inhibition and induction of glutathione S-transferases by flavonoids: possible pharmacological and toxicological consequences - Boušová, Iva; Skálová, Lenka (Drug metabolism reviews, 2012)
Many studies reviewed herein demonstrated the potency of some flavonoids to modulate the activity and/or expression of glutathione S-transferases (GSTs). Because GSTs play a crucial role in the detoxification of xenobiotics, their inhibition or induction may significantly affect metabolism and biological effects of many drugs, industrials, and environmental contaminants. The effect of flavonoids on GSTs strongly depends on flavonoid structure, concentration, period of administration, as well as on GST isoform and origin. Moreover, the results obtained in vitro are often contrary to the vivo results. Based on these facts, the revelation of important flavonoid-drug or flavonoid-pollutant interaction has been complicated. However, it should be borne in mind that ingestion of certain flavonoids in combination with drugs or pollutants (e.g., acetaminophen, simvastatin, cyclophosphamide, cisplatine, polycyclic aromatic hydrocarbons, chlorpyrifos, acrylamide, and isocyanates), which are GST substrates, could have significant pharmacological and toxicological consequences. Although reasonable consumptions of a flavonoids-rich diet (that may lead to GST induction) are mostly beneficial, the uncontrolled intake of high concentrations of certain flavonoids (e.g., quercetin and catechins) in dietary supplements (that may cause GST inhibition) may threaten human health.
Keywords: flavonoidy; Flavonoids; Enzyme Induction; Food-Drug Interactions; Animals; Humans; potravní doplňky; biotransformace; antioxidancia; Enzyme Inhibitors; inhibitory enzymů; Xenobiotics; Antioxidants; Liver; Biotransformation; Dietary Supplements; interakce mezi potravou a léky; zvířata; xenobiotika; glutathiontransferasa; enzymová indukce; lidé; játra; Glutathione Transferase